Transition From Nasogastric Tube to Oral Feeding: The Role of Parental Guided Responsive Feeding - Morag, Iris; Hendel, Yedidya; Karol, Dalia; Geva, Ronny; Tzipi, Strauss (Frontiers in Pediatrics, 2019)
Background and Objective: Strategies to transition preterm infants from tube to oral feeding vary greatly and the transition may take days to weeks. The study objective was to evaluate the effect of parental guided responsive feeding (PGRF) on this transition. Methods: We conducted a randomized controlled trial on infants born at <32 weeks gestation. The PGRF intervention was performed by parents, and included feeding intervals and volumes which were guided by the infants' behavioral cues of hunger and satiety. If a minimum volume was not taken orally, an intermediate volume was supplemented via nasogastric tube. The control group was traditionally fed (TF), with pre-planned volumes of intake and at given scheduled intervals. Results: The study comprised 67 infants (PGRF 32, TF 35). PGRF infants reached full oral feeding within less days (median 2 vs. 8 days, p = 0.001), at an earlier age (median 34.28 vs. 35.14 weeks, p < 0.001), returned to baseline weight gain at 35 weeks (1.77 ± 0.70 vs. 1.25 ± 0.63 g/kg/day, p = 0.002), were discharged earlier (36.34 ± 0.6 vs. 36.86 ± 0.9 weeks, p = 0.001), were more likely to be fed by their parents (p < 0.001), and experienced less apnea/bradycardia events at 34 weeks (median 3.5 vs. 9 per week p = 0.047) compared to the TF infants. The regression model demonstrated that independent variables predicted 43.7% of the variance of time to full oral feeding [F(9, 65) = 4.84 p < 0.001]. The only significant variable was feeding group (B = −6.43 p < 0.001); The PGRF infants were more likely to reach full oral feeding earlier. Conclusion: PGRF is safe, and associated with short-term advantages, higher parental engagement, and earlier discharge. Clinical Trial Registration: Identifier: SHEBA-12-9574-IM-CTIL; “Adjusted Individual Oral Feeding for Improving Short and Long Term Outcomes of Preterm Infants.”